2011
DOI: 10.1002/ppul.21501
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte zinc levels in children with bronchial asthma

Abstract: Zinc deficiency may be suspected to play a role in the pathogenesis, control, and severity of asthma because of its antioxidant, antiapoptotic, and anti-inflammatory effects. We aimed to investigate whether there was any relationship between erythrocyte zinc levels and childhood asthma. The erythrocyte zinc levels of 67 asthmatic and 45 healthy children were analyzed in this case-control study. The mean concentrations of erythrocyte zinc were 1215.8 ± 145.1 µg/dl in asthma patients and 1206.9 ± 119.5 µg/dl in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
(22 reference statements)
1
16
1
3
Order By: Relevance
“…Furthermore it has been shown that hair zinc levels are lower in children with recurrent wheeze compared with healthy controls and are negatively correlated with wheezing episodes in the last 6 months (21). Although erythrocyte zinc levels were not significantly decreased in asthma patients compared with a healthy group of children, there was a significant decrease in patients hospitalized with asthma attacks (22).…”
Section: Clinical Symptomsmentioning
confidence: 61%
“…Furthermore it has been shown that hair zinc levels are lower in children with recurrent wheeze compared with healthy controls and are negatively correlated with wheezing episodes in the last 6 months (21). Although erythrocyte zinc levels were not significantly decreased in asthma patients compared with a healthy group of children, there was a significant decrease in patients hospitalized with asthma attacks (22).…”
Section: Clinical Symptomsmentioning
confidence: 61%
“…Zinc deficiency may exacerbate airway inflammation in asthma. 47 Some studies show an association between low zinc levels and asthma, [48][49][50][51][52] while others contradict these findings, [53][54][55][56] and systematic review evidence is lacking. One study found no relationship between allergic rhinitis and plasma zinc and another study found no relationship between allergic rhinitis and dietary zinc intake.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is argued that anti-inflammatory and anti-oxidant agents will prevent the triggering of bronchoconstriction which constitutes the fundamental mechanism in asthma (4,6,9,12). It has been reported that zinc, which has anti-oxidant, anti-apoptotic, anti-inflammatory and anti-allergic properties, is important in dermatologic and respiratory diseases, while zinc deficiency plays an important role in the pathogenesis and severity of dermatologic and respiratory diseases (2,8,11). Because of its signi-ficant protective role in the airway epithelium, it is suggested that zinc deficiency may lead to an increase in epithelial damage and inflam-mation in airways (13).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is an essential dietary factor which has anti-inflammatory and anti-oxidant properties, and it is found in the contents of numerous cells of human body and structures of various enzymes (e.g. glutathione peroxidase and superoxide dismutase) in the respiratory tract (7,8). Moreover, zinc is considered to take part in the humoral and cellular immune response and it may play a role in the pathogenesis of asthma because of its anti-apoptotic and anti-inflammatory properties (2,9,10).…”
Section: Introductionmentioning
confidence: 99%